2014
DOI: 10.1371/journal.pntd.0003089
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Hexon Modified Adenoviral Vectors Integrated with gp83 Epitope Provides Protection against Trypanosoma cruzi Infection

Abstract: Background Trypanosoma cruzi is the causative agent of Chagas disease. Chagas disease is an endemic infection that affects over 8 million people throughout Latin America and now has become a global challenge. The current pharmacological treatment of patients is unsuccessful in most cases, highly toxic, and no vaccines are available. The results of inadequate treatment could lead to heart failure resulting in death. Therefore, a vaccine that elicits neutralizing antibodies mediated by cell-mediated immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…In the present study, analysis of the IgG subclasses from mice immunized with the adenoviral dendritic cell vaccine indicated that IgG1 was the dominant response in immunized BALB/c mice. In a previous study by Farrow et al (63), a strong IgG2b response induced by the Ad5-gp83 vaccine facilitated antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity in addition to eliciting neutralizing antibodies. Coordinated cellular (T H 1) and humoral (T H 2) responses are important for the effective clearance of intracellular pathogens by the adaptive immune system.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, analysis of the IgG subclasses from mice immunized with the adenoviral dendritic cell vaccine indicated that IgG1 was the dominant response in immunized BALB/c mice. In a previous study by Farrow et al (63), a strong IgG2b response induced by the Ad5-gp83 vaccine facilitated antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity in addition to eliciting neutralizing antibodies. Coordinated cellular (T H 1) and humoral (T H 2) responses are important for the effective clearance of intracellular pathogens by the adaptive immune system.…”
Section: Discussionmentioning
confidence: 98%
“…A method termed as "antigen capsidincorporation" based on homologous recombination is efficient in capsid modification of Ads and is used in Ad-based vaccine development. [32][33][34][35] Chimpanzee Ad-based vaccines for infectious diseases As described above, AdC has many ideal features as a vaccine vector compared to other vaccine vectors even the AdHu5 vector. Though clinical trials based on the AdHu5 vector are still being conducted, increasing numbers of pre-clinical or clinical trials ( Table 2).…”
Section: Methods For Generating Chimpanzee Ad Vectorsmentioning
confidence: 99%
“…, capsid shielding, has been researched for both reduction of hexon HVR-antigen exposure as well as for HAdV-5 vector tropism retargeting. 80 , 81 , 82 However, unless fused to the amino terminus of pIX, the insertional size of shielding moieties is limited, and this approach has demonstrated to severely impact the manufacturability of such “shielded” and/or “re-targeted” vectors given the low yield of replication-deficient HAdV-5 vectors obtained. 83 Another strategy to shield the antigenic HAdV-5 vector sites is being investigated whereby coating of HAdV-5 capsids using diverse materials, like polymers and lipidic envelopes is attempted.…”
Section: Challenges With the Development Of Hadv-5–based Medicinal Prmentioning
confidence: 99%